New features of Cuban endemic Pinguicula filifolia (Lentibulariaceae) and considerations on its habitat and ecology - Dominguez, Yoannis; Panfet Valdes, Cristina M.; Oliveira de Miranda, Vitor Fernandes [UNESP] (Elsevier Gmbh, Urban & Fischer Verlag, 2012)
Pinguicula filifolia C. Wright ex Griseb. is a carnivorous plant endemic in western Cuba. New features on the generation time habit and leaf morphology of this species are described and illustrated emphasizing its heteromorphic habit, based on studying living plants in nature and vouchers. A comparison of morphological characters of leaves among P. filifolia and its close relatives P. albida C. Wright ex Griseb. and P. cubensis Urquiola & Casper from west Cuba reveals morphological characters such as vertical position of the leaves, filiform blade, circinate apex and absence of edge curling. The description of new characteristics, such as an annual aestival habit and the presence of two kinds of carnivorous leaves during its growth cycle, emphasize the unique position of this species among Cuban taxa, all of them, so far, considered as "tropical homophyllous" within the genus. (C) 2012 Elsevier GmbH. All rights reserved.
Keywords: Carnivorous plant; ecology; Heteromorphic habit; Leaf morphology